2016
DOI: 10.1093/annonc/mdw370.34
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastasis in advanced colorectal cancer: Results from the South Australian metastatic colorectal cancer (SAmCRC) registry

Abstract: Objective: Brain metastasis is considered rare in metastatic colorectal cancer (mCRC); thus, surveillance imaging does not routinely include the brain. The reported incidence of brain metastases ranges from 0.6% to 3.2%. Methods:The South Australian mCRC Registry (SAmCRC) was analyzed to assess the number of patients presenting with brain metastasis during their lifetime. Due to small numbers, a descriptive analysis is presented. Results:Only 59 patients of 4,100 on the registry at the time of analysis had dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Overall, the prognosis for patients with BM from CRC is generally regarded as poor, and the median survival time is only a few months. [11,16,21,22] In this study, the median survival time was 7 months. Several studies found that the reliable factors predictive of a poor prognosis were recursive partitioning analysis class III, [18,23] KPS < 70, [10,11] diagnosis-specific graded prognostic assessment score: 0 to 1, [19] extracranial metastases, [13,24,25] treatment, [12,20,26,27] number of BMs, and the specific targeted therapy agents.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Overall, the prognosis for patients with BM from CRC is generally regarded as poor, and the median survival time is only a few months. [11,16,21,22] In this study, the median survival time was 7 months. Several studies found that the reliable factors predictive of a poor prognosis were recursive partitioning analysis class III, [18,23] KPS < 70, [10,11] diagnosis-specific graded prognostic assessment score: 0 to 1, [19] extracranial metastases, [13,24,25] treatment, [12,20,26,27] number of BMs, and the specific targeted therapy agents.…”
Section: Discussionmentioning
confidence: 70%
“…The survival time of patients with BM is quite poor, with a median survival of only 1 to 2 months without treatment. [3,16] In recent years, local treatments, such as several types of radiation (whole-brain radiotherapy [WBRT] and stereotactic radiosurgery), and neurosurgical resection have been widely applied to metastatic lesions. [5,13,[16][17][18][19] Previous research has shown that the blood-brain barrier blocks the passage of cytotoxic drugs, so the effect of chemotherapy is poor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 In recent studies, surgical excision of resectable colorectal cancer brain metastasis (CRCBM) has been increasingly reported to improve overall survival (OS). [7][8][9][10] Moreover, the survival of patients with all BM has been shown to be related to several patient characteristics, including age, presence of extracranial metastases, being underweight, and medical comorbidities. [10][11][12][13] Comorbidity indices, such as the Recursive Partitioning Analysis (RPA) class, the 5-item modified frailty index (MFI-5) and prognostic nutritional index (PNI), have been increasingly utilized in both oncological and neurosurgical practices to represent a comprehensive comorbidity status that aims to improve the prediction of prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, with advances in diagnostics and treatment techniques, the reported incidence increases to 9% [ 5 ]. Brain metastases are believed to occur by seeding of circulating tumor cells into the brain microvasculature; within this special microenvironment, tumor growth is encouraged and the penetration of systemic medical therapies is limited, this has been demonstrated in both clinical and preclinical studies [ 6–10 ]. BM from CRC is associated with dismal prognosis [ 1 , 11–13 ].…”
mentioning
confidence: 99%